Asymptotic decay of solutions to 3D MHD equations. (February 2016) - Wang, Yinxia
Abstract: In the very recent work Wang and Wang (2014) proved that the initial value problem for the three dimension incompressible MHD equations has a global solutions ( u, B ) ∈ C ( [ 0, ∞ ) ; χ − 1 ), provided that the norms of the initial data are bounded exactly by the minimal value of the viscosity coefficients. In this paper, we prove that global solutions u, B that was obtained in Wang and Wang (2014) is asymptotic to zero in sense of the norm of the space χ − 1 as time goes to infinity. Moreover, stability of global solutions is also discussed.